Correction to: Alternative graphical displays for the monitoring of epidemic outbreaks, with application to COVID-19 mortality - Thomas Perneger; Antoine Kevorkian; Thierry Grenet; Hubert Gallée; Angèle Gayet-Ageron (BMC Medical Research Methodology, 2020)
An amendment to this paper has been published and can be accessed via the original article.